Personal Assistance Services (PAS) for Workers with Disabilities: Views and Experiences of Rehabilitation Service Providers - Sita Misra; Louis E. Orslene; Richard T. Walls (Disability Studies Quarterly, 2007)
Personal Assistance Services (PAS) are defined as person-to-person services to assist people with disabilities with tasks they would perform if they did not have a disability. Traditionally, these services have focused on health care and activities of daily living. There has been minimal use of PAS in promoting employment and economic independence of people with disabilities. Research was conducted to determine the experiences and perceptions of rehabilitation service providers on the provision of PAS in the workplace. The study focused on (a) the definitional problems surrounding workplace PAS, (b) accessibility to PAS at the workplace, and (c) availability of resources (money and trained personal assistants). Views and experiences of rehabilitation service providers obtained through focus groups and a mail survey are presented. The rehabilitation service providers indicated that the success of providing PAS depended on establishing a strong, positive relationship with employers. Barriers to providing work-related PAS included lack of qualified assistants, transportation, and employers' lack of understanding of PAS.
Keywords: Personal Assistance Services; PAS; Employment; Disability